Strategi Tokoh Agama Dalam Menanamkan Moderasi Beragama Pada Komunitas Multiagama: Studi Kasus Desa Balun Lamongan - Amrullah, Hanif; Rofiq, Mohammad (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
Inter religious communication is a process of exchanging information and ideas between followers of different religions with the aim of promoting understanding, tolerance, and cooperation. In interfaith communication, it is important to avoid discussions that may lead to conflicts. Many examples of interfaith communication have been implemented, one of which can be seen in the relationship between Buddhism,Confucianism, and Taoism at the Eng An Kiong Temple in Malang City. Despite their different teachings, the relationship between these three beliefs is very good, which prevents any conflicts from happening. The relationship between these three beliefs has been established for quite some time and has never experienced any internal or external conflicts. The Islamic perspective on the relationship between these three beliefs can be seen from the perspective of interfaith tolerance. Islam teaches to respect the beliefs and differences of others. Interfaith tolerance is crucial in creating peace. Additionally, interfaith communication also has a positive impact on strengthening social relationships among followers of different religions. Through open and respectful dialogue, followers of different religions can learn to understand and accept their differences, thus creating a harmonious and peaceful environment among diverse communities.